The emerging role of leptin, Adiponectin and Visfatin in Ischemic/Hemorrhagic stroke - Ilhan, Nevin; Susam, Solmaz; Canpolat, Omer; Belhan, Oktay (Taylor & Francis Ltd, 2019)
Introduction: Adipose tissue acts as an active endocrine organ and may be involved in the biological mechanism of stroke. Adipokines can serve as key messenger of central energy and metabolic homeostasis and can contribute to the crosstalk between adipose tissue and brain. Recent research has offered vague data on the relationships between adipose tissue, adipokines, and vascular disorders. We aimed to investigate the clinical significance of serum leptin, adiponectin and visfatin levels and functional outcomes in patients with ischemic and hemorrhagic cerebrovascular diseases. Methods: Thirty-five patients with acurte intracerebral haemorrhage (ICH), 35 patients with acute ischemic stroke and 18 age- and sex-matched healthy controls were recruited. A sandwich ELISA was developed to measure the presence of serum adiponectin, leptin and visfatin levels. Results: Serum total cholesterol, low density lipoprotein, leptin, visfatin levels and systolic and diastolic blood pressure were higher and serum adiponectin levels were lower in patients at admission compared with healthy volunteers. Conclusion: According to the novel study, it was suggested that elevated serum leptin as well as visfatin and decreased adiponectin levels may be a sign of cerebrovascular disease and as part of the response occurring in stroke patients.
Keywords: Adiponectin; hemorrhagic; ischemic; leptin; visfatin